Using iPad tablets for self‐modeling with preschoolers: Videos versus photos. Issue 8 (23rd May 2017) - McCoy, Dacia M.; Morrison, Julie Q.; Barnett, Dave W.; Kalra, Hilary D.; Donovan, Lauren K.
Abstract: As technology becomes more accessible and acceptable in the preschool setting, teachers need effective strategies of incorporating it to address challenging behaviors. A nonconcurrent delayed multiple baseline design in combination with an alternating treatment design was utilized to investigate the effects of using iPad tablets to display video self‐modeling and activity photos for three preschoolers during circle time. During baseline, all three children demonstrated low levels of engagement and high levels of off‐task behavior compared to peers. The intervention phase consisted of alternating between showing the child the self‐video and photos prior to circle time. A child preference phase was conducted whereby each child self‐selected the video or photo prior to circle time. For all three children both videos and photos led to increased engagement and decreased off‐task behaviors. During the child preference phase, all three children selected the video most frequently. Social validity data demonstrated teacher and child preference for the video self‐modeling condition.